2021
DOI: 10.1080/24750263.2021.1905090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pesticides on Chelon labrosus (Risso, 1827) evaluated by enzymatic activities along the north eastern Sicilian coastlines (Italy)

Abstract: Pesticides are frequently applied to agricultural activities to improve harvest, in terms of yield and product quality. Useful tools for ecotoxicological studies of marine ecosystems are based on biomarker application on bioindicator key fish species. The main aim of the present study was to detect the potential presence of pesticides in a polluted coastal marine environment, namely Milazzo Gulf, situated in the north eastern coast of Sicily (Italy), by measuring the enzymatic activities of the ecotoxicologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 58 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Te results of their study showed changes in blood parameters and gills and liver tissue in acetamiprid-exposed fsh. Parrino et al [46,47] reported the toxicity efects of pesticides, their accumulations in aquatic environments and their threats for nontarget organisms, especially human. In the present study, the analyzing of liver and gills of groups (50-200 mg•L −1 of acetamiprid) revealed various tissue damages upon 96 h exposure to acetamiprid.…”
Section: Discussionmentioning
confidence: 99%
“…Te results of their study showed changes in blood parameters and gills and liver tissue in acetamiprid-exposed fsh. Parrino et al [46,47] reported the toxicity efects of pesticides, their accumulations in aquatic environments and their threats for nontarget organisms, especially human. In the present study, the analyzing of liver and gills of groups (50-200 mg•L −1 of acetamiprid) revealed various tissue damages upon 96 h exposure to acetamiprid.…”
Section: Discussionmentioning
confidence: 99%
“…The fish were anesthetized with 75 mg/L of clove oil in bucket for 4 min [ 47 , 48 ]. Blood samples were drawn from the caudal vein using a sterile syringe and then transferred in EDTA microtubes [ 49 , 50 , 51 ] for hematological analysis. Tissues of gills, livers, and kidneys were collected, properly processed, and then stored at −20 °C until the analyses for metal accumulation and oxidative stress enzymes were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Although Hg toxicity has been the topic of several studies [ 17 , 18 , 19 ], clarifying the mechanisms of dietary MeHg toxicity in fish remains challenging. Fish have been widely used in ecotoxicological studies as worthy sentinel organisms [ 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] due to their ability to accumulate and metabolize different contaminants in their tissues and to produce valid and measurable responses (biomarkers) when exposed to stressful conditions, such as the presence of Hg.…”
Section: Introductionmentioning
confidence: 99%